Implementation of State Policy in the Field of Guardianship and Trusteeship: Regional Aspect - Koroleva, Elvira V.; Volynchuk, Yana A. (Cuestiones Políticas, 2020)
The objective of the work is to review the implications of the implementation of state guardianship policy in the Primorsky territory of the Russian Federation. The institution of the family is the most important factor for the development of the child’s personality; its role is constantly growing in the development and education of children. Without a doubt, the family is a natural educational environment for a child who leaves his mark on his behavior and character. A special place in the modern legal system is occupied by the aspect of the right of the child and the protection of the interest that is left without the care of the parents. Methodologically, use was made of the documentary research technique close to legal hermeneutics. It is concluded that the guardianship and guardianship bodies perform a series of important functions for any civilized state, namely: identification of people who need to establish one of the forms of guardianship (adoption); adoption of such persons, as well as increased supervision of the guardian, the activities of the adoptive parents and of persons authorized by the state to care for those who need their help.